Effect of additive manufacturing method and build angle on surface characteristics and Candida albicans adhesion to 3D printed denture base polymers. (January 2022) - Li, Ping; Fernandez, Pablo Kraemer; Spintzyk, Sebastian; Schmidt, Franziska; Beuer, Florian; Unkovskiy, Alexey
Abstract: Objectives: To investigate the influence of additive manufacturing method and build angle on surface characteristics and Candida albicans ( C. albicans ) adhesion to 3D printed denture base polymers. Methods: Specimens of 3D printing denture base polymers were prepared by two printers, namely, stereolithography (SLA, Form 3B) and digital light processing technology (DLP, Solflex 350 plus). Three build angles were used: 0°, 45°, and 90°. Surface topography was examined by scanning electron microscopy. Also, arithmetical mean height (Sa ) values were calculated. An adhesion test was performed to observe initial C. albicans adhesion to the specimens. The data were statistically analyzed using the two-way analysis of variance and Tukey's multiple comparison test. Results: The data of Sa values had statistically significant differences, which were mainly determined by the main factor of build angle ( p  < 0.05). Moreover, the quantitative results of C. albicans adhesion exhibited no significant differences: printing techniques ( p  = 0.7794) and build angle ( p  = 0.0589), respectively. Conclusions: Surface roughness was significantly influenced by the build angle rather than by the AM method. Whereas, AM method (SLA and DLP) and build angle (0°, 45°, and 90º) had no impacts on the C. albicans adhesion to the 3D printed denture bases. Clinical Significance: Build angle dominates the surface roughness and topography of the 3D printed denture polymers. Our results indicate that C. albicans' adhesion might not be influenced by AM method and build angle. Graphical abstract: Image, graphical abstract